PSYCHOMETRIC EVALUATION OF SYMPTOMS AND CLINICAL DYNAMICS OF SCHIZOPHRENIA IN DEPENDING ON CONSTITUTIONALLY-MORPHOLOGICAL TYPE OF THE PATIENTS - F. F. Mikilev; E. G. Kornetova; O. A. Lobacheva; A. N. Kornetov; A. V. Semke (Бюллетень сибирской медицины)
The purpose of this study was to research the psychometrical parameters and the clinical-dynamic features of patients with schizophrenia in depending on their constitutionally-morphological type.Material and methods. The examination of 86 patients with schizophrenia who are hospitalized at Department of endogenous mental disorders of Mental Health Research Institute was conducted. The study included patients of age from 18 to 65 years old with prescription of catamnesis at least 1 year and whose state at the time of examination corresponded to the diagnostic criteria for schizophrenia from the ICD-10 (International Classification of Diseases 10th Revision). The examination included filling in a modified version of Basic Card of Standardized Description of the Patient with Schizophrenia and his Relative, Positive and Negative Syndrome Scale (PANSS), Clinical Global Impression Scale (CGI). In addition to that patients were examined using anthropometrical method by V.V. Bunak. Statistical significance of differences in the data was evaluated using the Kruskal – Wallis test by ranks, the Mann – Whitney U-test, and Pearson’s chi-squared test. The correlation analysis was performed by the Spearman’s rank correlation test. The K-Means Cluster Analysis was used to determine of the qualitative interrelation and conjugation between the clinical characteristics of the examined.The results of the study revealed that many parameters of the functioning in these patient groups have statistically significant differences. Use of the K-Means Cluster Analysis was allowed to reveal the internal structure of the data, to group the individual observations according to their degree of similarity.Conclusions. The obtained data leads to the assumption that the constitutionally-morphological type of patients has an impact on the clinical course of schizophrenia, as well as their adaptation abilities. Asthenic constitutionally-morphological type is a factor of adverse clinical dynamic of schizophrenia and associates with persistent negative disorders and suicidal actions. Overall, this study continues integrative anthropological trend in psychiatry and lays the foundation for further study of the constitutional factors effect on the course of schizophrenia. The obtained results can serve as a model for studying the facade symptoms in general schizophrenia spectrum disorders and be used in the development of individually oriented therapeutic and rehabilitation programs in clinical psychiatry.